Profil Socio-Économique Et Démographique Des Populations Issues De La Migration Sur Le Littoral Ôdjoukrou. (Sud De La Côte d’Ivoire) - Mel Mélèdje Melaine; Aloko N’guessan Jérôme (European Scientific Journal, ESJ, 2018)
The rural country of ôdjoukrou, or lôdjoukrou, is part of the Ivorian coastline. It is a space with enormous economic potential. Agricultural space, the boom in the plantation economy, will mobilize a large foreign workforce. This paper focuses on analyzing the socio-economic and demographic characteristics of populations resulting from migration. To meet the objective of this study, the methodological approach used is based on a literature search. We also used a field survey motivated by a questionnaire administered to 1000 migrants. An interview was also conducted with the chieftaincies of the various localities. The study reveals that the majority of migrants are West African immigrants with 79.8%. The majority of migrants, estimated at 38%, work in agriculture. In addition, the study allows us to relate the type of activity carried out in relation to the migrant's geographical origin. Most unhealthy incomes are considered satisfactory, to the point of encouraging regular monthly transfers to other family members of the starting spaces.